2001
DOI: 10.1097/00001756-200107030-00016
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 plays an important protective role in experimental autoimmune encephalomyelitis

Abstract: Increasing evidence shows that oxidative stress plays an important role in the pathogenesis of experimental autoimmune encephalomyelitis (EAE), an animal model of the human disease, multiple sclerosis (MS). Heme oxygenase-1 (HO-1) is a heat shock protein induced by oxidative stress. HO-1 metabolizes heme to the antioxidant bilirubin and carbon monoxide, and represents a powerful endogenous defensive mechanism against free radicals in many diseases. However, the role of this important enzyme in EAE remains unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 25 publications
2
58
1
2
Order By: Relevance
“…As our previous study demonstrated, bilirubin system activity substantially increased as EAE progressed and reached its maximum at the peak of clinical sign (28,29). Even after cessation of clinical disease, a high level of bilirubin system expression was still found in slowly resolving lesions (28,29), which suggests that this endogenous inducible system may contribute to animals' recovery from EAE. We then treated acute EAE in Lewis rats with ZnPP, a specific inhibitor of the bilirubin-producing enzyme HO-1.…”
Section: Plp-immune Cd4mentioning
confidence: 62%
“…As our previous study demonstrated, bilirubin system activity substantially increased as EAE progressed and reached its maximum at the peak of clinical sign (28,29). Even after cessation of clinical disease, a high level of bilirubin system expression was still found in slowly resolving lesions (28,29), which suggests that this endogenous inducible system may contribute to animals' recovery from EAE. We then treated acute EAE in Lewis rats with ZnPP, a specific inhibitor of the bilirubin-producing enzyme HO-1.…”
Section: Plp-immune Cd4mentioning
confidence: 62%
“…The administration of a HO-1 inducer to normal mice results in suppressions of T cell-mediated cytotoxicity and Th1-mediated cytokine production and decreases in the lymphoproliferative alloresponse and differentiation of CTLs (30). HO-1 inducer also prevents the induction of T cell-mediated experimental autoimmune encephalomyelitis in rats (31). In accord with these observations, we recently demonstrated that human CD4 ϩ T cells express HO-1 and that HO-1-overexpressing Jurkat T cells tend to display lower proliferative response.…”
Section: Discussionmentioning
confidence: 99%
“…187 MS hastalığının hayvan modelinde yapılan bir çalışmada, hemin verildiğinde hastalık modelinde iyileşme sağlanmıştır. 188 Başka bir çalışmada yine aynı modelde, HO-1 ve CO'nun otoimmün nöroinflamasyonu iyileştirdiği gösterilmiştir. 189 Diğer yandan MS plaklarındaki demir birikimini, HO-1'in aşırı eksprese olmasıyla ilişkilendiren çalışmalar da bulunmaktadır.…”
Section: Multiple Sklerozunclassified